The Relationship Between the Intensity of Gadget Use and the Social Development of Early Childhood in Ambacang Kamba Village, Pesisir Selatan Regency - Afri Nanda; Vevi Sunarti (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2026)
Limitations of social development in children aged 5–6 years in Ambacang Kamba Village, Pesisir Selatan Regency, are the background for carrying out this research. The high levels of gadget use in early infancy are thought to be linked to this disorder, which may limit children's chances for face-to-face social engagement with classmates and adults. The objectives of this study include several things, namely: (1) to determine the level of gadget use in early childhood in Ambacang Kamba Village; (2) to describe the condition of social development of early childhood in the area; (3) to examine the relationship between the intensity of gadget use and the social development of early childhood. This study uses a quantitative approach with a correlational design. The study population consists of 30 parents who have children aged 5–6 years in Ambacang Kamba Village. Based on calculations using the Slovin formula with a 5% margin of error, a sample of 28 parents was obtained as study respondents. Data collection was conducted through questionnaires. Next, the data were analyzed using percentage analysis to describe each variable, and the The Spearman Rank correlation coefficient (Rho) was used to test the relationship between the two variables. The research results indicate that the intensity of children's device use is high, while their social development is low. Furthermore, correlation analysis reveals a meaningful association between the level of device usage and early childhood social development. To support optimal social development, parents are advised to limit the duration of electronic device use by children and encourage direct interaction with others.